Hepatitis B, C and human immunodeficiency virus knowledge among the general greek population: results from the Hprolipsis nationwide survey - Sylvia Kaskafetou; Argiro Karakosta; Vana Sypsa; Natasa Kalpourtzi; Magda Gavana; Apostolos Vantarakis; George Rachiotis; Grigoris Chlouverakis; Grigoris Trypsianis; Paraskevi V. Voulgari; Yannis Alamanos; George Papatheodoridis; et al. (BMC, 2022)
Abstract Background Although several studies on hepatitis B (HBV), C (HCV) and human immunodeficiency virus (HIV) infection have been conducted in Greece, little is known on the knowledge level of the Greek population towards these three infections. Our aim was to assess the knowledge level of the adult Greek general population about the HBV, HCV and HIV. Methods Data were derived from the first general population health survey, Hprolipsis. The sample was selected by multistage stratified random sampling. A standardized questionnaire was administered by trained interviewers during home visits. A knowledge score was constructed based on responses to 17 per infection selected items and categorized in three levels; high (12-17 correct replies) medium (6-11) and low (0-5). Among 8,341 eligible individuals, 6,006 were recruited (response rate: 72%) and 5,878 adults (≥ 18 years) were included in the analysis. The statistical analysis accounted for the study design. Results Only 30.4%, 21.6%, and 29.6% of the participants had a high overall knowledge level of HBV, HCV and HIV, respectively. These low percentages were mainly attributed to the high levels of misconception about transmission modes (65.9%, 67.2%, and 67.9%, respectively). Results showed that increasing age and living out of the big metropolitan cities were associated with decreased odds of having higher knowledge. Female gender, higher education level, higher monthly family income, higher medical risk score, history of testing and being born in Greece or Cyprus, were associated with increased odds of having higher knowledge. Conclusions There are significant knowledge gaps in the Greek general population regarding modes of transmission, preventive measures and treatment availability for HBV, HCV and HIV. There is an urgent need for large scale but also localized awareness activities targeted to less privileged populations, to fill the gaps in knowledge and increase population engagement in preventive measures.